Experimentation of Problem Based Learning (PBL) Model on Student Learning Motivation and Achievement on Circle Material - Yunia Sari; Sutrisno Sutrisno; Sugiyanti Sugiyanti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
This study aims to determine whether the motivation and learning achievement of class VIII students who get treatment with the Problem Based Learning model is better than the conventional learning model. This type of research is quantitative research. In this study using a questionnaire to determine student learning motivation and tests to determine student learning achievement. The sampling technique with Cluster Random Sampling from the population of class VIII students. Data collection techniques with documentation, tests, and questionnaires. Data analysis techniques in this study were Multivariate Normality Test, Homogeneity Test of Covariance Matrix, T2 Hotelling Trace Test and independent t-test. From the initial data the daily test scores and learning motivation questionnaire scores are used to determine whether the conditions of the two classes are balanced. From the final data of the experimental and control classes with data analysis techniques such as preliminary data, it can be concluded that motivation and learning achievement of students using the Problem Based Learning model is better than conventional learning models.